Evolution of the Stock of Total Organic Carbon of Soil under the Culture of Cassava (Manihot Crantz esculenta) Installed in no Incineration in a Forest Fallow of the Yakonde Set (Y2) in Relation to the One of the Old Surrounding Secondary Forest of the Re - Kombele M; Motondo M; Motosia A; Kolela B; Ugencan D; Lifafu H; Kakuni J; Kombele F; Kombele FM (Britain International of Exact Sciences (BIoEx) Journal, 2022)
The objective pursued in this work is to try to put in evidence the ecological role of the cassava culture installed by no burning of the biomass on the management of the stock of total organic carbon of soil. Thus, an extent of 0,48 ha has been delimited and has been subdivided in 24 parcels in which were installed 24 pedological pits and where 48 samples of soil that means 24 samples no - unsettled and 24 unsettled others, were appropriated in the slices of 0-20 and 20-40 cm of depth these samples served for the determination of the total organic matter, the total organic carbon, the obvious density and of the stock in carbon of soil to seven months of age of the culture of five varieties of cassava. Five cultivars of cassava to know Disanka, Obama, Zizila, Me vuazi and Nsansi have been installed in a fallow forest enhancement by no - incineration of the biomass and an old secondary forest taken like reference, situated in the Yakonde set (Y2) in the Tray Isalowe in Yangambi, RD Congo. The results gotten during our experimentation reveals a relative an impact in the management of the stock of soil carbon by the different cultivars of cassava, with the exception of the Zizila varieties (T3) and Nsansi (T5) in relation to the old secondary forest taken like witness even though that, the analyses statistical attest non meaningful differences between the worth of carbon stock observed so much in soil under the different varieties of cassava that under the old secondary forest. Nevertheless, the no - incineration decorated the most suitable fashion of enhancement of soil in general in the optics of the lasting management of the stock of organic carbon of soil in the agrosystèmes of the tropics and of the region of Yangambi in particular.